1987
DOI: 10.3354/meps035015
|View full text |Cite
|
Sign up to set email alerts
|

Digestive enzymes of the anchovy Engraulis capensis in relation to diet

Abstract: Digestive enzymes of the anchovy Engraulis capensis in relation to diet' Department of Microbiology, University of Cape Town, Rondebosch 7700, South Africa Institute for Marine Environmental Research, Prospect Place, Plymouth PL1 3DH, United Kingdom ABSTRACT: The anchovy Engraulis capensis (Glch.) is capable of exploiting both diatoms and Crustacea as a food resource. Much of the crustacean exoskeletal rnatenal passes into the hindgut after initial dsruphon in the stomach. Both laminarinase and cl-amylase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the present investigation, a considerable population of bacterial symbionts has been isolated from the alimentary tracts of the Chinese grass carp, C. idella and tilapia, O. mossambica and some of the strains exhibit significant cellulolytic activity. The microbial populations within the digestive tract of fish are rather immense (Trust, Bull, Currie & Buckley 1979; Rimmer & Wieb 1987; Seiderer, Davis, Robb & Newell 1987; Sutton & Clements 1988; Clements 1991; Luczkovich & Stellwag 1993; Ringø & Strøm 1994; Kandel, Horn & Van Antwerp 1994; Clements & Choat 1995), with a number of microorganisms much higher than in the surrounding water, indicating that the digestive tract provides favourable ecological niches for these organisms (Trust & Sparrow 1974; Horsley 1977; Austin & Al‐Zahrani 1988; Sakata 1990). While the digestive tract of endotherms is colonized mainly by obligate anaerobes (Finegold, Sutter & Mathisen 1983), the predominant bacterial genera/species isolated from most fish guts have been aerobes or facultative anaerobes (Trust & Sparrow 1974; Horsley 1977; Sakata 1990; Bairagi et al 2002; Ghosh et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation, a considerable population of bacterial symbionts has been isolated from the alimentary tracts of the Chinese grass carp, C. idella and tilapia, O. mossambica and some of the strains exhibit significant cellulolytic activity. The microbial populations within the digestive tract of fish are rather immense (Trust, Bull, Currie & Buckley 1979; Rimmer & Wieb 1987; Seiderer, Davis, Robb & Newell 1987; Sutton & Clements 1988; Clements 1991; Luczkovich & Stellwag 1993; Ringø & Strøm 1994; Kandel, Horn & Van Antwerp 1994; Clements & Choat 1995), with a number of microorganisms much higher than in the surrounding water, indicating that the digestive tract provides favourable ecological niches for these organisms (Trust & Sparrow 1974; Horsley 1977; Austin & Al‐Zahrani 1988; Sakata 1990). While the digestive tract of endotherms is colonized mainly by obligate anaerobes (Finegold, Sutter & Mathisen 1983), the predominant bacterial genera/species isolated from most fish guts have been aerobes or facultative anaerobes (Trust & Sparrow 1974; Horsley 1977; Sakata 1990; Bairagi et al 2002; Ghosh et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have analysed for chitinolytic enzyme activity in fish larvae, although chitinase has been reported in the eggs and larvae of red sea bream Pagrus major (Kono et al 1987) and from the late yolk sac stage and beyond in trout Salmo gairdnen (Lindsay 1985). Even in adult fish which feed on crustaceans, chitin does not appear to be fully utilized (Seiderer et al 1987). Lindsay (1984) concluded that, in adult fish, the primary function of chitinase may be for the initial chemical disruption of the exoskeleton of prey.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although chitinolytic activity has been observed in the digestive tract of several fish species (e.g. Yoshida & Sera 1970;Sakata et al 1980;Benmouna et al 1986;Seiderer et al 1987;Danulat 1987), it is not clear how far chitin is effectively assimilated and utilized for metabolic requirements. Indeed, several authors have observed chitinous exoskeletons lingering in the gut of fish (e.g.…”
mentioning
confidence: 99%